Epidithiodiketopiperazines Inhibit Protein Degradation by Targeting Proteasome Deubiquitinase Rpn11. Issue 11 (15th November 2018) - Li, Jing; Zhang, Yaru; Da Silva Sil Dos Santos, Bruno; Wang, Feng; Ma, Yuyong; Perez, Christian; Yang, Yanling; Peng, Junmin; Cohen, Seth M.; Chou, Tsui-Fen; Hilton, Stephen T.; Deshaies, Raymond J.
Summary: The 26S proteasome is the major proteolytic machine for breaking down cytosolic and nuclear proteins in eukaryotes. Due to the lack of a suitable assay, it is difficult to measure routinely and quantitatively the breakdown of proteins by the 26S proteasome in vitro . In the present study, we developed an assay to monitor proteasome-mediated protein degradation. Using this assay, we discovered that epidithiodiketopiperazine (ETPs) blocked the degradation of our model substrate in vitro . Further characterization revealed that ETPs inhibited proteasome function by targeting the essential proteasomal deubiquitinase Rpn11 (POH1/PSMD14). ETPs also inhibited other JAMM (JAB1/MPN/Mov34 metalloenzyme) proteases such as Csn5 and AMSH. An improved ETP with fewer non-specific effects, SOP11, stabilized a subset of proteasome substrates in cells, induced the unfolded protein response, and led to cell death. SOP11 represents a class of Rpn11 inhibitor and provides an alternative route to develop proteasome inhibitors. Graphical Abstract: Highlights: An HTS assay is developed to measure protein breakdown activity of 26S proteasome It allows measurement of 26S proteasome activity in cell or tissue lysate ETPs inhibit JAMM proteases including the proteasomal deubiquitinase Rpn11 ETPs block proliferation of cancer cells including those resistant to bortezomib Abstract : The deubiquitinase Rpn11 is a component of 26S proteasome, is required for proteasome activity, and is a new target for proteasome inhibition in cancer. We develop an assay that enables measurement of the proteasome's protein breakdown activity in cell lysate and identifies ETPs as a new class of Rpn11 inhibitors.